2011
DOI: 10.1542/peds.2010-3037
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Forensic Evidence From Pediatric Victims of Sexual Assault

Abstract: Body samples should be considered for children beyond 24 hours after assault, although the yield is limited. Physical examination findings do not predict yield of forensic laboratory tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…11,12 Importantly, the presence of significant physical findings does not predict recovery of foreign DNA and should not be the basis for collecting forensic evidence. 10 Additionally, DNA can still be recovered following genital wiping after the event. 12 At this time, forensic evidence collection is recommended for sexual contact that may have resulted in the exchange of biologic material within 24 hours in prepubertal children and within 72 hours in adolescents.…”
Section: Examinationmentioning
confidence: 99%
“…11,12 Importantly, the presence of significant physical findings does not predict recovery of foreign DNA and should not be the basis for collecting forensic evidence. 10 Additionally, DNA can still be recovered following genital wiping after the event. 12 At this time, forensic evidence collection is recommended for sexual contact that may have resulted in the exchange of biologic material within 24 hours in prepubertal children and within 72 hours in adolescents.…”
Section: Examinationmentioning
confidence: 99%
“…Interestingly, testing and prophylaxis were not affected by presence of injury. As many pediatric victims of sexual assault will not have evidence of injury on exam, 13, 14 it is important that care not vary based on these findings. In fact, in our population, just over one-third of the patients had injuries noted at the time of the ED visit; higher than what has been previously reported in the literature, which has ranged from 21–24%.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study was conducted that determined the relationship between time of sexual assault and the time frame in which the yield of evidence using DNA amplification is valid supported an extended time frame for FEK collection from children [44]. Findings showed that body swabs collected from children beyond 24 hours after assault still yielded evidence.…”
Section: Figure 2cmentioning
confidence: 99%